Artist-run Europe practice, projects, spaces - Cullen, Mark 1960-; Bowman, Jason E.; Bronson, AA 1946-; Collins, Noelle; Connor, Valerie 19XX-; Kopp, Céline; Williams, Alun 1961-; Laws, Joanna; Lomme, Freek; Morley, Megs; Murphy, Gavin; Wade, Gavin 1971-; et al. (Onomatopee, 2016)
Part how-to manual, part history, and part socio-political critique, 'Artist-Run Europe' looks at the conditions, organisational models, and role of artist-led practice within contemporary art and society. The aim is to show how artist-run practice manifests itself, how artist-run spaces are a distinctive and central part of visual art culture, and how they present a complex, heterogeneous, and necessary set of alternatives to the art institution, museum and commercial gallery. In a self-reflexive, critically questioning process, contributions by Jason E. Bowman, AA Bronson, Noelle Collins, Valerie Connor, Mark Cullen, Céline Kopp, Joanna Laws, Freek Lomme, Megs Morley, Gavin Murphy, Transmission Gallery, Gavin Wade, and Katherine Waugh, discuss and analyse areas such as: What position do artist-run spaces occupy within the field of contemporary art today?